2001
DOI: 10.1023/a:1012559724283
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We studied functional disturbances in hemopoietic microenvironment and cytokine production by stromal sublayer in long-term bone marrow cultures and peripheral blood macrophages from patients with various forms of myelodysplastic syndrome. Production of factors stimulating the growth of normal erythroid and granulocytic precursors by cells of the stromal sublayer from patients with refractory sideroblast anemia and refractory anemia with excess blasts is impaired compared to cells from healthy donors. The medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The imprints were put on a roentgen fi lm and developed. Several immunoblots (2)(3)(4) were performed for each patient. Albumin served as the control for electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The imprints were put on a roentgen fi lm and developed. Several immunoblots (2)(3)(4) were performed for each patient. Albumin served as the control for electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…These fi ndings are consistent with published data and results of our previous experiments, which illustrate dysfunction of the stroma in MDS patients. For example, MDS patients are characterized by a reduced number of fi broblast precursors in the bone marrow [1] and low capacity of the hemopoietic microenvironment to maintain hemopoiesis in long-term cultures [1,2] and monolayer cultures of the bone marrow [6]. Recent cytogenetic studies revealed the presence of chromosomal aberrations in mesenchymal cells from patients with MDS and AL [4,5].…”
Section: Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Elstner et al showed that marrow from MDS patients formed poor adherent stromal layers [61], which may affect proliferation of MDS precursor cells [62,63]. Also, long-term bone marrow cultures from patients with MDS revealed impaired production of cytokines, such as IL-3 or hepatocyte growth factor [61,62,64–66]. The fact that healthy donor HSC, nevertheless, engraft in the marrow of MDS patients provides support for the concept that alterations in MDS stroma are dependent upon the presence of clonal MDS cells and are reversible upon their elimination.…”
Section: Murine Xenotransplantation Models Of Mdsmentioning
confidence: 99%